2018
DOI: 10.1167/tvst.7.6.31
|View full text |Cite
|
Sign up to set email alerts
|

Reproducibility of Macular Vessel Density Calculations Via Imaging With Two Different Swept-Source Optical Coherence Tomography Angiography Systems

Abstract: PurposeTo evaluate the reproducibility of vessel density calculations using different binarization methods obtained via two commercially available swept-source optical coherence tomography angiography (SS-OCTA) systems.MethodsHealthy volunteers were imaged using two swept-source optical coherence tomography angiography (SS-OCTA) devices, PLEXElite and Triton. SS-OCTA examinations were performed using a 3 × 3-mm volume scan pattern centered on the fovea. A total of six methods were used for binarization in Imag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
36
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 40 publications
(37 citation statements)
references
References 32 publications
1
36
0
Order By: Relevance
“…Such reference data can then be compared with measurements made in a variety of retinal diseases to detect different anomalies ideally in early disease stages. 28 Our data reveal mean VDs in the foveal subfield of 22.1% ± 5.0% and 19.9% ± 6.3% in the SCP and DCP, respectively, the difference being significant (P < .001). 5,6,[20][21][22][23][24] In this study, a commercial SS-OCTA device equipped with new software was used to quantify VD in the macula.…”
Section: Discussionmentioning
confidence: 49%
See 1 more Smart Citation
“…Such reference data can then be compared with measurements made in a variety of retinal diseases to detect different anomalies ideally in early disease stages. 28 Our data reveal mean VDs in the foveal subfield of 22.1% ± 5.0% and 19.9% ± 6.3% in the SCP and DCP, respectively, the difference being significant (P < .001). 5,6,[20][21][22][23][24] In this study, a commercial SS-OCTA device equipped with new software was used to quantify VD in the macula.…”
Section: Discussionmentioning
confidence: 49%
“…27 Other authors have also reported good reproducibility for the use of different OCTA devices (RTVue Avanti, Fremont, California; ICC ≥ .873) 6 or the Plex Elite (Carl Zeiss Meditec, Jena, Germany; ICC ≥ .70). 28 Our data reveal mean VDs in the foveal subfield of 22.1% ± 5.0% and 19.9% ± 6.3% in the SCP and DCP, respectively, the difference being significant (P < .001). Using the spectral domain (SD)-OCTA RTVue-XR Avanti (Optovue, Fremont, California) with external software, Shahlaee et al also noted a higher VD in 122 healthy subjects for the foveal region at the level of the SCP than DCP (32% ± 3.2% vs 27% ± 5.2%; P < .001).…”
Section: Discussionmentioning
confidence: 49%
“…Yarmohammedi A et al 20,39 and Takusagawa HL et al 29 used a spectral-domain OCTA device and Takusagawa HL et al 29 analysed the macular microvasculature using a 6 mm ×6 mm OCTA image. Moreover, our previous study showed that the difference in the OCTA device used and the vessel density quantification method (binarisation method) affected the VD quantification 40 .…”
Section: Discussionmentioning
confidence: 99%
“…Two groups compare available macular vessel density algorithms [18,20]. Shoji et al [20] assess binarization algorithms in ImageJ (National Institutes of Health, Bethesda, MD, USA) on data obtained from two OCTA systems, while Rabiolo et al [18] compare seven previously published quantification algorithms, concluding that the estimated densities are significantly di↵erent for each algorithm.…”
Section: Related Workmentioning
confidence: 99%
“…Two groups compare available macular vessel density algorithms [18,20]. Shoji et al [20] assess binarization algorithms in ImageJ (National Institutes of Health, Bethesda, MD, USA) on data obtained from two OCTA systems, while Rabiolo et al [18] compare seven previously published quantification algorithms, concluding that the estimated densities are significantly di↵erent for each algorithm. Both studies therefore recommend using the same quantification algorithm in longitudinal follow-up, and note that vessel density is dependent on both the OCTA device, the acquisition size, and the post-processing algorithm, and hence comparisons to other studies or databases should be done with care.…”
Section: Related Workmentioning
confidence: 99%